Laboratory assessment of cellulose fibre in Stone Mastic Asphalt - Lilian Gungat; Nurul Ariqah Ispal; Joedansen Ak. Delon; Jeffrey Koh K.T (Malaysian Construction Research Journal, 2021)
Stone Mastic Asphalt(SMA) is referred to as a gap-graded Hot Mix Asphalt and has a stone skeleton structure that resists permanent deformation. There are insufficient studies that focus on the issue of the SMA using the sandstone type of aggregate. In this study, cellulose fibre was added at 0, 0.2, 0.4 and 0.6% of the total aggregate weight and evaluated for the volumetric properties, strength properties, optimum bitumen content, bitumen draindown and resilient modulus. Volumetric properties which include voids in mixture, voids in mineral aggregates, voids filled with bitumen, and bulk density of SMA after the addition of cellulose fibre showed improvements after further addition of the cellulose fibre. The optimum bitumen content showed an increment ranging from 5.9 to 6.6% after inclusion of cellulose fibre. Remarkable improvement in bitumen drain down from 0.041 to 0.008% was observed with inclusion of cellulose fibre content increased. The resilient modulus of SMA increased as the cellulose fibre content increased until the optimal cellulose fibre content and decreased after further addition of cellulose fibre. Based on the laboratory evaluations of SMA, the most suitable percentage of cellulose fibre that was recommended for road construction is 0.2%. The proposed cellulosed fibre content is based on the most optimal values in volumetric properties, strength properties and bitumen draindown which is economical and performance effective for the road construction application. © 2021, Construction Research Institute of Malaysia. All rights reserved.